2011
DOI: 10.1177/1741826711398431
|View full text |Cite
|
Sign up to set email alerts
|

Are HIV patients undertreated? Cardiovascular risk factors in HIV: results of the HIV-HEART study

Abstract: The prevalence of CRFs remains high in an HIV-infected population. CRF management of HIV-infected patients deserves further improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 36 publications
6
53
1
2
Order By: Relevance
“…This finding was consistent with the suboptimal use of statins observed in the D.A.D. cohort and in the HIV-HEART study, but different than in the HOPS in which 81-87% of those with elevated LDL-c or non-HDL-c recommended for therapy were receiving treatment [25,26,34]. However, therapy in the HOPS data was defined much more broadly than in the current study and included prescription of one of numerous different lipid-lowering agents (statins, ezetimibe, bile acid sequestrants, nicotinic acid) and documentation of exercise.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding was consistent with the suboptimal use of statins observed in the D.A.D. cohort and in the HIV-HEART study, but different than in the HOPS in which 81-87% of those with elevated LDL-c or non-HDL-c recommended for therapy were receiving treatment [25,26,34]. However, therapy in the HOPS data was defined much more broadly than in the current study and included prescription of one of numerous different lipid-lowering agents (statins, ezetimibe, bile acid sequestrants, nicotinic acid) and documentation of exercise.…”
Section: Discussionsupporting
confidence: 79%
“…The 2004 National Education Program Adult Treatment Plan III (NCEP ATPIII) guidelines helped HIV clinicians determine lifestyle and pharmacological interventions based on patients' lipid profiles and their 10-year risk of developing CHD using the 2002 Framingham CHD-related mortality, but HIV-infected individuals are frequently undertreated for hyperlipidemia and associated CHD risk factors [24][25][26][27]. However, some recent reports of decreasing CHD-associated mortality in select HIV populations have postulated that more aggressive control of CHD risk factors such as high blood pressure and abnormal lipid levels may account for the declines in some populations [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the high prevalence of risk factors for cardiovascular diseases such as smoking, arterial hypertension, and elevated triglycerides and VHDL cholesterol among persons with HIV/ AIDS 18 , studies suggest that HAART and the chronic inflammation characterizing HIV infection are associated with greater risk of cardiovascular diseases in persons with HIV/AIDS 19,20 . Some studies have shown greater risk of cardiovascular events in persons with HIV/AIDS and on HAART as compared to those without treatment 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…[13]. Auch die dauerhafte Einnahme von Medikamenten besitzt möglicherweise eine herzschädigende Wirkung.…”
Section: Introductionunclassified